2018
DOI: 10.7554/elife.35176
|View full text |Cite
|
Sign up to set email alerts
|

A surface proton antenna in carbonic anhydrase II supports lactate transport in cancer cells

Abstract: Many tumor cells produce vast amounts of lactate and acid, which have to be removed from the cell to prevent intracellular lactacidosis and suffocation of metabolism. In the present study, we show that proton-driven lactate flux is enhanced by the intracellular carbonic anhydrase CAII, which is colocalized with the monocarboxylate transporter MCT1 in MCF-7 breast cancer cells. Co-expression of MCTs with various CAII mutants in Xenopus oocytes demonstrated that CAII facilitates MCT transport activity in a proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 87 publications
1
81
0
1
Order By: Relevance
“…A similar type of interaction was also observed between intracellular CAII and MCT1/MCT4 (52)(53)(54)(55). Because CAII catalytic activity is not required to facilitate MCT transport function, it was hypothesized that CAII might utilize parts of its intramolecular proton pathway to function as a proton antenna for the transporter (55)(56)(57). Protonable residues with overlapping Coulomb cages could form proton-attractive domains and could share a proton at a very fast rate, exceeding the upper limit of diffusion-controlled reactions (58,59).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…A similar type of interaction was also observed between intracellular CAII and MCT1/MCT4 (52)(53)(54)(55). Because CAII catalytic activity is not required to facilitate MCT transport function, it was hypothesized that CAII might utilize parts of its intramolecular proton pathway to function as a proton antenna for the transporter (55)(56)(57). Protonable residues with overlapping Coulomb cages could form proton-attractive domains and could share a proton at a very fast rate, exceeding the upper limit of diffusion-controlled reactions (58,59).…”
mentioning
confidence: 84%
“…CAII binds MCT1 and MCT4 via a cluster of three glutamic acid residues within the transporters' C-terminal tails (MCT1, 489 EEE (62), and MCT4, 431 EEE (63)). In both cases, the two outer glutamic acids form hydrogen bonds with the histidine at position 64 in CAII (57).…”
mentioning
confidence: 99%
“…According to the IPA analysis, we found that carbonic anhydrase II (CA2) was dysregulated between the two comparison (C/DN group and SN/DN group). CA2, a zinc metal enzyme, carries out the reversible hydration of carbon dioxide, and plays a key role in adjusting the pH of tumour microenvironment [2934]. It is frequently abnormally expressed in different cancers [3541].…”
Section: Resultsmentioning
confidence: 99%
“…In such an environment, efficient proton handling seems crucial for protoncoupled lactate transport across the membrane. We have previously suggested that intracellular and extracellular carbonic anhydrases can function as "proton antennae" for MCTs by mediating the rapid exchange of protons between the transporter pore and the surrounding protonatable residues [29, [64][65][66][67]. In CAIX, proton transfer between MCT and surrounding protonatable residues seems to be mediated by acidic residues within the enzyme's proteoglycan-like domain [30].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional antibody staining of cultured breast cancer cells was described in detail previously [29,66]. The antibodies used for conventional antibody staining were identical to the antibodies used for the PLA and were used in the same concentration.…”
Section: Antibody Staining In Cultured Cancer Cellsmentioning
confidence: 99%